Comorbidities associated with anatomical and functional myocardial impairments assessed by 13 N-ammonia positron emission tomography. (14th October 2021) - Alexanderson-Rosas, E; Espinola-Zavaleta, N G; Antonio-Villa, N E; Gurrola-Luna, H
Abstract: Background: There has been an increase in the number of comorbidities in that predispose to ischemic heart disease in developing countries. Nevertheless, the identification of associated risk factors could unveil impairments within myocardial function Purpose: We aimed to assess the prevalence and factors associated with reduced modifications of LVEF (>5%), ischemia (SDS ≥6 pts), reduced coronary flow reserve (≤2.5 pts) and coronary artery obstruction (≥50%) using a positron emission tomography–computed tomography. Methods: A cross-sectional study of patients with clinical suspicious of angina who attended the PET/CT unity in a faculty of medicine was designed. We designed a clinical questionnaire to capture information regarding clinical history of comorbidities, angina, medication use and lifestyle habits. A myocardial perfusion study (MPS) was performed to identify myocardial ischemia, infarction, dyssynchrony and reduced coronary flow reserve. Logistic regression analyses were performed to identify associated factors. Results: 1273 patients underwent a PET/CT study; 66.1% (n=841) were male with a median age of 62.4 (±12.7) years. In our population, 36.4% (n=464) reported 1 or 2 comorbidities, 31.6% (n=402) 3 to 4 and 4.7% (n=60) more than 5; arterial hypertension (46.9%), dyslipidemia (43.9%), and diabetes (20.8%) were highly prevalent. Angina (34.4%) and palpitations (13%) were the most frequent symptoms at evaluation (Table 1). We found that that the presence of age ≥65 years, history of myocardial infarction, male sex, precordial chest pain, agrarians in chest pain, familiar history of myocardial infarction and comorbidities such as diabetes, arterial hypertension and obesity were associated with impairments in LVEF, ischemia, reduced coronary flow reserve and coronary artery obstruction (Figure 1). Conclusions: The presence of comorbidities in our population is high. The identification of a cardiovascular profile using associated factors would allow early identification of those patients with alterations in myocardial function parameters. Funding Acknowledgement: Type of funding sources: None.